Effective avoidance of a functional spect-perfused lung using intensity modulated radiotherapy (IMRT) for non-small cell lung cancer (NSCLC): an update of a planning study. - Lavrenkov, K; Singh, S; Christian, J; Partridge, M; Nioutsikou, E; Cook, G; Bedford, J; Brada, M (2009)
IMRT and 3-dimensional conformal radiotherapy (3-DCRT) plans of 25 patients with non-small cell lung (NSCLC) were compared in terms of planning target volume (PTV) coverage and sparing of functional lung (FL) defined by a SPECT perfusion scan. IMRT resulted in significant reduction of functional V(20) and mean lung dose in stage III patients with inhomogeneous hypoperfusion. If the dose to FL is shown to be the determinant of lung toxicity, IMRT would allow for effective dose escalation by specific avoidance of functional lung.